Knowledge, attitude, and behavior regarding hydration of fluid intake of a university’s students in Jakarta - Luciana B Sutanto; Tasya Choiriah Putri; Helena Fabiani; Gracia JMT Winaktu (World Nutrition Journal, 2023)
Adequate body fluid is beneficial for maintaining physiology, cognitive function, and concentration, which are important for students. The purpose of this study was to determine knowledge, attitude, and behavior regarding hydration and fluid consumption and fluis intake of university students in Jakarta.